A Systematic Literature Review (SLR): Implementasi Audiobook pada Pembelajaran di Sekolah Dasar - Arissona Dia Indah Sari, Arissona Dia Indah Sari; Tatang Herman; Wahyu Sopandi; Al Jupri (Jurnal Elementaria Edukasia, 2023)
Audiobooks are a form of technological development that allows students and teachers to access information more easily and flexibly. This study uses the Systematic Literature Review (SLR) method by analyzing relevant previous studies and providing a clear and comprehensive description of the use of audiobooks in the context of learning in schools. This research can provide practical recommendations for teachers and schools in implementing audiobooks as part of their learning strategies, as well as other researchers who are interested in researching audiobooks in learning. The results of this study indicate that the use of audiobooks in school learning has been extensively researched and implemented in various contexts and subjects in various countries. Of the 100 articles identified, 72% were written in English, and this research shows that the use of audiobooks in learning is mostly implemented in language subjects. In addition, the type of research that is most often used is qualitative, while the subjects that are most often the focus of research are students, especially to develop listening and reading competencies. Indonesia was also identified as the country that most often conducts research on the implementation of audiobooks in classroom learning.